Politeness Strategy to Potray Positive and Negative Face Responses in Vladimir Putin’ Speech on “The Reason Why Russian Attacked Ukraine” - Abiyyu Alamsyah; Cut Novita Srikandi; Yenni Hasnah (English Teaching and Linguistics Journal (ETLiJ), 2023)
This study discusses the Politeness Strategy used by Vladimir Putin in his speech on The Reason Why Russia Attacked Ukraine. The purpose of the study is to comprehend what kind of Politeness Strategy Theory used by Vladimir Putin, how positive and negative facial responses are, and what the message is conveyed in his Speech. The qualitative research was applied in this research. The data analysis was shaped into the table by grouping the Politeness Strategy Theory after that the data was analyzed to answer the research problem. From this study, the researcher found out that there are 27 utterances that are included in the Politeness Strategy. The results of this study show that Vladimir Putin threats more Positive Face than Negative face. This result shows that there are main strategies used by Vladimir Putin in his speech, are: (7 utterances of Bald on Record), (9 utterances of Positive Politeness), (8 utterances of Negative Politeness), and (3 utterances of Off-Record). The results show that the positive Politeness Strategy was frequently used in this study because he wanted to make a good relationship with all the audiences in order to minimize the social distance between them.